Динамічний мікроклімат і енергоощадність - Возняк, Орест (Видавництво Національного університету «Львівська політехніка», 2002)
In this article the results of incoming jet characteristics determination investigations at variable regime of its arival into the room are presented. Analytic equations for jet parameters calculation at case of dynamic microclimate creation in aroom are obtained. Two-factors dependency of air jet velocity against running coordinate and time is presented as a chart. Quantity estimation of microclimate providing system save energy and efficiency of heat (cool) at dynamic microclimate case in comparison with a constant regime is done.